Noncovalent Interactions of π Systems with Sulfur: The Atomic Chameleon of Molecular Recognition. (28th December 2017) - Motherwell, William B.; Moreno, Rafael B.; Pavlakos, Ilias; Arendorf, Josephine R. T.; Arif, Tanzeel; Tizzard, Graham J.; Coles, Simon J.; Aliev, Abil E.
Abstract: The relative strength of noncovalent interactions between a thioether sulfur atom and various π systems in designed top pan molecular balances was determined by NMR spectroscopy. Compared to its oxygen counterpart, the sulfur atom displays a remarkable ability to interact with almost equal facility over the entire range of π systems studied, with the simple alkene emerging as the most powerful partner. With the exception of the O⋅⋅⋅heteroarene interaction, all noncovalent interactions of sulfur with π systems are favoured over oxygen.